DESTINATION DEVELOPMENT: ENHANCING SMALL TOURISM FIRMS COMPETITIVENESS - Nikolovski, Branko (Horizons - International Scientific Journal, 2020)
This paper examines the tourism destination as a dynamic system of tourism components interplays. Systemic model of destination competitiveness includes analysis of comparative advantages (tourism resources) and competitive advantages (ability to use tourism resources effectively) of a given destination compared to its competitors. Destination development strategies that enhance Small Tourism Firms (STFs) competitiveness are brand value, agglomeration effects, differentiation strategy, cooperation, cost disease, state incentives, applying knowledge –based economic models and activities, clusters, alliances, networking, cooperation, and developing entrepreneurial support organizations (ESO’s). System view of tourism helps us to match tourism destination with appropriate supply and demand component development strategies. This approach enhances destination’s capacity to develop and integrate value-added products and services which in turn strengthens destination market position, while carefully spending its resources. Thus, destinations apply specific processes which transform assets (natural resources and infrastructures) into tangible economic results.